Marginal Life-Cycle Greenhouse Gas Emissions of Electricity Generation in Portugal and Implications for Electric Vehicles - Garcia, Rita (2016)
This article assesses marginal greenhouse gas (GHG) emissions of electricity generation in Portugal to understand the impact of activities that affect electricity demand in the near term. In particular, it investigates the introduction of electric vehicles (EVs) in the Portuguese light-duty fleet considering different displacement and charging scenarios (vehicle technologies displaced, EV charging time). Coal and natural gas were identified as the marginal energy sources, but their contribution to the margin depended on the hour of the day, time of year, and system load, causing marginal emissions from electricity to vary significantly. Results show that for an electricity system with a high share of non-dispatchable renewable power, such as the Portuguese system, marginal emissions are considerably higher than average emissions. Because of the temporal variability in the marginal electricity supply, the time of charging may have a major influence on the GHG emissions of EVs. Off-peak charging leads to higher GHG emissions than peak charging, due to a higher contribution of coal to the margin. Furthermore, compared to an all-conventional fleet, EV introduction causes an increase in overall GHG emissions in most cases. However, EV effects are very dependent on the time of charging and the assumptions about the displaced technology.